Syzygium aromaticum (clove) essential oil: An alternative for the sanitization of citrus fruit in packinghouses - Soraggi Battagin, Tiago [UNESP]; Nicolas Caccalano, Mario [UNESP]; Dilarri, Guilherme [UNESP]; Felipe Cavicchia Zamuner, Caio [UNESP]; Alleoni, Natália [UNESP]; Leonardo Saldanha, Luiz [UNESP]; Bacci, Maurício [UNESP]; Ferreira, Henrique [UNESP] (Hindawi, 2021)
Citrus canker is a quarentenary disease caused by Xanthomonas citri subsp. citri (X. citri). Thus, sanitization of fresh fruit is a necessary measure before any commercial activity. Therefore, we evaluated the clove essential oil (CEO), as an alternative sanitizer for the disinfection of citrus fruit in packinghouses. Tests in vitro and in vivo were carried out to determine the cell inhibitory concentration and to verify the efficacy of the oil for the disinfection of citrus fruits. In in vitro tests, CEO was able to inhibit X. citri when used at 0.75% (v/v). In experiments that simulate the sanitization process used in packinghouses, 5% CEO was as effective as the recommended sanitization product based on sodium hypochlorite. GC-MS results showed a high presence of eugenol derivatives as the major compounds of CEO. All results proved that CEO is a potential sanitizer that could be used as an alternative to sodium hypochlorite. Novelty impact statement: Experimental evidence shows that the clove essential oil (CEO) has the same sanitization efficacy as sodium hypochlorite, which makes of CEO an alternative sanitizer for the decontamination of citrus fruits to be exported to the European Union. CEO is a safer and more sustainable sanitizer for the postharvest disinfection of citrus fruit.